Racialised capitalism, decoloniality and the university: an exploration of the colour line and colonial unreason in higher education - Tegama, Natalie (Frontiers in Sociology, 2023)
Over the last decade, there has been an increase in calls to address important questions on race and decolonisation within the university, administratively, pedagogically, and socially. This study investigates the relationship between the university, the coloniser, and the colonised during the colonial era and the afterlife. It aims to demonstrate that the university has made the act of abstraction and theorisation central across disciplines in a way that shears theoretical principles from the historical contexts they emerge from, distancing them from the purposes, people, and interests they were meant to serve, as well as the populations they were meant to dispossess and disempower. The study provides a conceptual framework for deconstructive analysis of the university’s pedagogical operations and societal function with the view to elucidate the university’s colonial and racial blind spots, notably, with a reliance on disciplinary narratives from development, international relations, and international law to offer tentative answers to the questions of decolonial praxis, the decolonial scholar, and coloniality in the contemporary university.